Evaluasi Peraturan Daerah Nomor 8 Tahun 2019 Tentang Pengawasan Kelebihan Muatan Angkutan Barang Di Kabupaten Siak: (Studi Kasus Dampak Pelanggaran Kelebihan Muatan Angkutan Barang Di Kampung Buantan Besar) - Muhairil, Oddie Dilham; Nur Laila Meilani (Journal of Research and Development on Public Policy, 2023)
Transportation is a very important means. Realizing the role of transportation, therefore traffic and road transportation must be organized to create orderly traffic and transportation services, including by controlling overloaded goods cars. In order to create traffic order, Siak Regency Regional Regulation Number 8 of 2019 concerning Supervision of Overloading of Goods Transport was issued, which is carried out by the Siak Regency DISHUB and the Police. The purpose of this research is to first find out and analyze the evaluation of Regional Regulation Number 8 of 2019 concerning Overloading of Goods Transport in Siak Regency. The second is to find out and analyze the impact of the Goods Transport Overloading violation in Buantan Besar Village. The theory used is William N. Dunn's theory using 6 indicators, namely: Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. This research uses a type of qualitative research that is descriptive analysis. Using interview, observation and documentation data collection techniques. The results of this study found that the implementation of regional regulations handled by the Siak Regency Transportation Service was quite satisfactory or good enough even though there were still some deficiencies in it, such as limited facilities and infrastructure, budget, human resources and time to carry out supervision. So improvements are still needed in implementing this regional regulation. So that the process of implementing the Evaluation of Regional Regulation of Siak Regency Number 8 of 2019 Concerning Supervision of Excess Cargo Goods can run optimally and optimally, various factors and needs must always be improved to achieve the goals of these regulations.